Comprehensive Study of Stacked Nanosheet-Type Channel Based on Junctionless Gate-All-Around Thin-Film Transistors - Yu-Ru Lin (IEEE, 2019)
As technology develops, the stacked nanosheet (NS) structure demonstrates promise for use in future technology nodes. This study demonstrated the excellent performance of stacked-NS channels with junctionless gate-all-around thin-film transistors and compared the electrical characteristics of single-NS and stacked-NS structures. The performance of the multi-gate and gate-all-around transistors was then further analyzed. The stacked gate-all-around thin-film transistor exhibited superior performance and excellent temperature design flexibility. In brief, the stacked gate-all-around structure for thin-film transistors structure has the potential to overcome the challenges associated with downscaling.